Incidence of Acute Ischemic Stroke With Visible Arterial Occlusion: A Population-Based Study (Dijon Stroke Registry). Issue 7 (July 2020) - Duloquin, Gauthier; Graber, Mathilde; Garnier, Lucie; Crespy, Valentin; Comby, Pierre-Olivier; Baptiste, Laura; Mohr, Sophie; Delpont, Benoit; Guéniat, Julien; Blanc-Labarre, Christelle; Hervieu-Bègue, Marie; Osseby, Guy-Victor; et al.
Abstract : Background and Purpose: Because of several methodological limitations, previous studies focusing on the prevalence of large vessel occlusion in ischemic stroke (IS) patients provided conflicting results. We evaluated the incidence of IS with a visible arterial occlusion using a comprehensive population-based registry. Methods: Patients with acute IS were prospectively identified among residents of Dijon, France, using a population-based registry (2013–2017). All arterial imaging exams were reviewed to assess arterial occlusion. Annual incidence rates of IS (first-ever and recurrent events) and IS with a visible occlusion were calculated. Results: One thousand sixty cases of IS were recorded (mean age: 76.0±15.8 years, 53.9% women). Information about arterial imaging was available in 971 (91.6%) of them, and only preexisting dementia was independently associated with having missing information (odds ratio=0.34 [95% CI, 0.18–0.65], P =0.001). Among these patients, 284 (29.2%) had a visible arterial occlusion. Occlusion site was the anterior circulation in 226 patients (23.3% of overall patients with available data) and the posterior circulation in 58 patients (6.0%). A proximal occlusion of the anterior circulation was observed in 167 patients (17.2%). The crude annual incidence rate of total IS per 100 000 was 138 (95% CI, 129–146). Corresponding standardized rates were 66 (95% CI, 50–82) to the World Health Organization and 141 (95% CI, 118–164) to the 2013 European populations. The crude annual incidence rate of IS with a visible arterial occlusion per 100 000 was 37 (95% CI, 33–41) and that of IS with a proximal occlusion of the anterior circulation was 22 (95% CI, 18–25). Corresponding standardized rates were 18 (95% CI, 10–26) and 10 (95% CI, 8–13) to the World Health Organization population, and 38 (95% CI, 26–50) and 23 (95% CI, 19–26) to the 2013 European population, respectively. Conclusions: These results will be helpful to plan the need for thrombectomy-capable stroke center resources. Abstract : Supplemental Digital Content is available in the text.